Dark loneliness : selected stories - Mahānti, Gopīnātha (Postgraduate Dept. of English, Utkal Univ., 2012)
Tadpa -- Ants -- Bed of arrows -- The roadblock -- Two warriors -- The solution -- The shelter -- Light and shadow